Asuhan Akupunktur Pada Klien Tinitus di Klinik SKNC Bogor - Kiki Hendrawan; Chantika Mahadini; Puspo Wardoyo; Leny Candra Kurniawan (Malahayati Nursing Journal, 2026)
ABSTRACT Tinnitus is the perception of sound in the absence of an external sound source. It is a symptom that can be associated with various causes and triggering factors, most commonly occurring alongside sensorineural hearing loss, particularly bothersome tinnitus without clear otologic pathology. Acupuncture works by stimulating points around the ear and along meridians related to the ear, thereby helping to normalize cochlear function and the auditory nervous system. This case study aimed to determine the benefits of acupuncture care for clients with tinnitus at the SKNC Clinic Bogor. The study was conducted as a single case study over six therapy sessions involving one male participant aged 50 years who experienced tinnitus. Data collection techniques included observation (Wang), interviews (Wen), listening and smelling (Wen), and palpation (Qie), in accordance with the standards of Traditional Chinese Medicine. The selection of acupuncture points was based on the Kidney Yin Deficiency syndrome, with therapeutic principles focused on eliminating tinnitus and tonifying Kidney Yin. The therapy evaluation results showed gradual and consistent improvement, with the primary complaint of tinnitus no longer being perceived, additional complaints such as dizziness and sleep disturbances resolving, and the participant’s overall condition improving. Keywords: Tinnitus, Acupuncture Therapy, Kidney Yin Deficiency.  ABSTRAK Tinitus adalah persepsi suara tanpa adanya sumber suara eksternal. Tinitus merupakan gejala yang dapat dikaitkan dengan berbagai penyebab dan faktor pencetus, paling sering bersamaan dengan gangguan pendengaran sensorineural, terutama tinitus yang mengganggu tanpa patologi telinga yang jelas. Akupunktur bekerja dengan menstimulasi titik di sekitar telinga dan meridian yang berhubungan dengan telinga, sehingga membantu menormalkan fungsi koklea dan sistem saraf auditorik. Penelitian studi kasus ini bertujuan untuk mengetahui manfaat Asuhan Akupunktur pada Klien Tinitus di Klinik SKNC Bogor. Penelitian dilakukan dalam bentuk studi kasus tunggal selama enam sesi terapi pada satu orang partisipan laki-laki berusia 50 tahun yang mengalami Tinitus. Teknik pengumpulan data meliputi observasi (Wang), wawancara (Wen), pendengaran dan penciuman (Wen), dan perabaan (Qie) sesuai standar ilmu pengobatan Tiongkok. Pemilihan titik akupunktur didasarkan pada sindrom Yin Ginjal Defisien dengan prinsip terapi yang diterapkan adalah hilangkan Tinitus dan Tonifikasi Yin Ginjal. Hasil evaluasi terapi menunjukkan adanya perbaikan yang bertahap dan konsisten, keluhan utama berupa tinitus sudah tidak dirasakan lagi, keluhan tambahan seperti pusing dan gangguan tidur menghilang, serta kondisi umum partisipan menjadi lebih baik. Kata Kunci: Tinitus, Terapi Akupunktur, Yin Ginjal Defisien.